INCREASING INTEREST, ACTIVITY, AND LEARNING OUTCOMES OF SOCIOLOGY THROUGH THE THINK PAIR SHARE LEARNING MODEL - Salamah; Tinursani, Deni (Program Magister Pendidikan IPS UPY, 2025)
Abstract This study aims to explainincreasing interest, activity, and learning outcomes of Sociology through the think pair share learning model in class XI students of SMA Negeri 1 Sedayu for the 2019/2020 school year. This research is a classroom action research. The subjects in this study were class XI students, totaling 32 people. with general procedures covering the stages of planning, acting, observing, and reflecting. The data collection method is observation, questionnaires, documentation, and learning outcomes tests. The results of this study indicate that the application of think pair share can increase the interest, activity, and learning outcomes of Sociology in students. This increase can be proven by an increase in interest in learning which at the pre-cycle stage was 0% to 3.137% in cycle 1, then in cycle 2 it became 78.13% with a minimum category of good; increased activitystudy which at the pre-cycle stage was 0% to 40.63% in cycle 1, then increased to 90.63% with a minimum category of good in cycle 2; and an increase in learning outcomes at the pre-cycle stage by 12.50% to 59.38% in cycle 1, then increasing to 100% in cycle 2. Keywords: Interest in learning, active learning, learning outcomes, think pair share